Extracellular DNA Traps: Origin, Function and Implications for Anti-Cancer Therapies - Mamtimin, Medina; Pinarci, Akif; Han, Chao; Braun, Attila; Anders, Hans-Joachim; Gudermann, Thomas; Mammadova-Bach, Elmina (Frontiers in Oncology, 2022)
Elevated levels of extracellular DNA serve as markers in liquid biopsies to determine individual diagnosis and prognosis in cancer patients. Cell death or active release from various cell types, including immune cells can result in the release of DNA into the extracellular milieu. Neutrophils are important components of the innate immune system, controlling pathogens through phagocytosis and/or the release of neutrophil extracellular traps (NETs). NETs also promote tumor progression and metastasis, by modulating angiogenesis, anti-tumor immunity, blood clotting and inflammation and providing a supportive niche for metastasizing cancer cells. Besides neutrophils, other immune cells such as eosinophils, dendritic cells, monocytes/macrophages, mast cells, basophils and lymphocytes can also form extracellular traps (ETs) during cancer progression, indicating possible multiple origins of extracellular DNA in cancer. In this review, we summarize the pathomechanisms of ET formation generated by different cell types, and analyze these processes in the context of cancer. We also critically discuss potential ET-inhibiting agents, which may open new therapeutic strategies for cancer prevention and treatment.